Fabrication and characterization of silicon nanowires with MACE method to influence the optical properties. (2022) - Kashyap, Vikas; Chaudhary, Neeru; Goyal, Navdeep; Saxena, Kapil
Abstract: We are presenting here fabrication of silicon (Si) nanowires (NWs) arrays by using Si (1 0 0) wafer as substrate, by metal assisted chemical etching (MACE) method. The Si-NWs growth on the Si wafer has been done by using etching time of 45 min in etching solution of hydrogen fluoride and hydrogen peroxide. X-ray diffraction (XRD) has been used for the structural analysis of NWs to estimate the crystalline size, micro-strain, dislocation density of fabricated nanostructures. The surface morphology of Si-NWs array has been studied through field effect scanning electron microscopy (FE-SEM). The optical properties like energy band gap of fabricated Si-NWs has been carried out through UV–Vis diffuse reflectance spectroscopy (UV DRS) and photoluminescence (PL) spectroscopy.